The Effect of Demographic Variables on Price Sensitivity of Customers A Field Study - Nassar, Yehia; Gad, Ghada; Kortam, Wael (Archives of Business Research, 2021)
This study aims to improve understanding of the relationship between some customer demographic variables which are gender, income level, family life cycle and age. And price sensitivity of customers which is an individual difference variable describing how individual consumers show their reactions to changes in price levels. This study will be applied in Fast Moving Consumer goods (FMCG) industry in Egypt. Fast Moving Consumer goods are the products which have high usage frequency, have limited shelf life (up to two years max) for example Biscuits, chocolates, personal care, hair care and dental care products. The consumption of these products is high and that’s why these products move fast from retailers to consumers.